How about Some Muscle? Charles H. McCloy's Contributions to Physical Education in China between 1913 and 1926. Issue 15 (2nd November 2019) - Vertinsky, Patricia; Ramachandran, Aishwarya; Wang, Bo
Abstract: The work of American physical educator Charles H. McCloy during his stay in China between 1913 and 1926 illuminates the nexus of nationalism, modernity, and the training of the body that emerged in international reform movements. It provides an overview of his early interest and training in physical education in the United States before accepting a position with the YMCA in China. Never at a loss for words, rarely short of an opinion, McCloy's work in China as Mai Kele during a critical period of political change is particularly interesting for the approaches to physical education training he offered to the Chinese in their own language and his efforts to promote his strongly held views about fitness, muscular development and the education of the body. 'Going to China', he reflected in later years, 'was one of the great experiences of my life'. Although he fell out of favor with the YMCA in 1921, he remained in China until 1926 to work for the National Southeastern University where many of his valuable efforts were incorporated into the wider educational project of modernizing China. While he never returned, he retained contact with Chinese students for the rest of his lengthy career.